ACCURACY EVALUATION OF VARIOUS SATELLITE IMAGERY PRODUCTS FOR LARGE SCALE TOPOGRAPHIC MAPPING - N. Gahlot (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2018)
DEM and ortho-imageries are building blocks for topographic mapping and satellite imageries are prime source of data for inaccessible terrain. When the required mapping scale is of the order 10k or higher, the accuracy needed is also of higher order. It becomes imperative to evaluate the accuracy of available high resolution DEMs and corresponding imageries to provide quality products for mapping. The present study is encouraged by the fact that not every place of our earth is accessible, so an assessment of satellite data products is required for precise mapping. Here, the accuracy assessment has been carried out in terms of RMSE, SD, CE90 and LE90 of various products viz. Carosat-1, Cartosat-2E, Worldview-2 (WV), Vricon, Pleiades, ALOS-World-3D (AW3D) ASTER, SRTM with Yahoo image. GCPs acquired by DGPS field survey were used to evaluate the products. The results have demonstrated that Vricon 0.5 m ortho-image provides the best RMSE (3.42) and CE90 (4.65); however, WV and Vricon DEM turns out to be best with RMSE of 2.20 m and 2.90 m respectively. Both products are suitable for large scale topographic mapping. The data can be used for inaccessible terrain where GCPs are not available. However, Cartosat-1 and Cartosat-2E can be used where good GCPs are available. The outcome of study can be used for planning of data suitability for scale variant mapping and inaccessible terrain mapping.